Variation in phenotype and virulence among enzootic and panzootic amphibian chytrid lineages - Becker, C. G. [UNESP]; Greenspan, S. E.; Tracy, K. E.; Dash, J. A.; Lambertini, C.; Jenkinson, T. S.; Leite, D. S.; Toledo, L. F.; Longcore, J. E.; James, T. Y.; Zamudio, K. R. (Elsevier B.V., 2017)
The Global Panzootic Lineage of the fungus Batrachochytrium dendrobatidis (Bd-GPL) is threatening amphibians worldwide. In contrast, four lineages (Bd-Brazil, Bd-CH, Bd-Cape, and Bd-Korea) that diverged early in the history of Bd have not yet been directly linked to amphibian declines. Bd likely evolves in response to strong selective pressure imposed by hosts and the environment, leading to differences among pathogen phenotypes and genotypes that may directly affect virulence. Here, We report on variation in phenotype, genotype, and virulence of Bd-Brazil and Bd-GPL. Specifically, we (i) used a controlled infection experiment to compare virulence between one Bd-Brazil and three Bd-GPL isolates on a North American amphibian host (Lithobates sylvaticus), (ii) tested for relative phenotypic and genotypic differentiation among Bd isolates from Brazil, and (iii) tested for possible correlations between environmental variables and Bd phenotypes. We found substantial variation in virulence among Bd-GPL isolates and found that our Bd-Brazil isolate showed virulence comparable to an average North American Bd-GPL. North American hosts infected with a Bd-GPL isolate from Panama did not show significant mortality. Bd phenotypes varied significantly across sampling locations; these phenotypes were neither spatially clustered nor correlated with any environmental variables. Additionally, we found a surprising lack of correlation between genotypic divergence and zoospore and zoosporangium sizes in our sample. Although Bd-Brazil was less virulent infecting L. sylvaticus than one Bd-GPL isolate, this endemic lineage still caused-50% mortality in our experimental Ndrth American hosts, This indicates that Bd-Brazil has the potential to kill amphibians if introduced to na ve wild populations. Our findings underscore that characterizing virulence of multiple Bd isolates and lineages is important for understanding the evolutionary history and diversity of Bd. (C) 2016 Elsevier Ltd and British Mycological Society. All rights reserved.
Keywords: Declines; Anurans; Chytridiomycosis; Environmental pressure